Potential Mitigation and Restoration Actions in Ecosystems Impacted by Seabed Mining - Cuvelier, Daphne; Gollner, Sabine; Jones, Daniel O. B.; Kaiser, Stefanie; Arbizu, Pedro Martínez; Menzel, Lena; Mestre, Nélia C.; Morato, Telmo; Pham, Christopher; Pradillon, Florence; Purser, Autun; Raschka, Uwe; et al. (Frontiers in Marine Science, 2018)
Mining impacts will affect local populations to different degrees. Impacts range from removal of habitats and possible energy sources to pollution and smaller-scale alterations in local habitats which, depending on the degree of disturbance, can lead to extinction of local communities. While there is a shortage or even lack of studies investigating impacts that resemble those caused by actual mining activity, the information available on the potential long-lasting impacts of seabed mining emphasise the need for effective environmental management plans. These plans should include efforts to mitigate deep-sea mining impact such as avoidance, minimisation and potentially restoration actions, to maintain or encourage reinstatement of a resilient ecosystem. A wide range of mitigation and restoration actions for deep-sea ecosystems at risks were addressed. From an ecological point of view, the designation of set-aside areas (refuges) is of utmost importance as it appears to be the most comprehensive and precautionary approach, both for well-known and lesser studied areas. Other actions range from the deployment of artificial substrates to enhance faunal colonisation and survival to habitat recreation, artificial eutrophication, but also spatial and temporal management of mining operations, as well clever mining machine construction to minimise plume size on the sea floor, toxicity of the return plume and sediment compression. No single action will suffice to allow an ecosystem to recover, instead combined mitigation/restoration actions need to be considered, that will depend on the specific characteristics of the different mining habitats and the resources hosted (polymetallic sulphides, polymetallic nodules and cobalt-rich ferromanganese crusts). However, there is a lack of practical experience regarding mitigation and restoration actions following mining impacts which severely hamper their predictability and estimation of their possible effect and success. The actions proposed here are not exhaustive or exclusive but are worth taking into consideration. Further research is necessary to fully encompass their potential and contribution to possible mitigation or restoration of the ecosystem.